Gut Microbiota Signature Among Asian Post-gestational Diabetes Women Linked to Macronutrient Intakes and Metabolic Phenotypes - Hasain, Zubaidah; Raja Ali, Raja Affendi; Abdul Razak, Shairah; Azizan, Kamalrul Azlan; El-Omar, Emad; Razalli, Nurul Huda; Mokhtar, Norfilza Mohd (Frontiers in Microbiology, 2021)
Aberrant gut microbiota dysbiosis in women with a previous history of gestational diabetes mellitus (post-GDM) was comparable to that in adults with type 2 diabetes mellitus (T2DM). Nonetheless, potential relationships between diet, gut microbiota, and metabolic phenotypes in post-GDM women after delivery are yet to be discovered. In this research, we assessed the relationship of the macronutrient intakes, gut microbiota composition, and metabolic phenotypes (i.e.anthropometrics and glycemic control) in post-GDM women with and without postpartum glucose intolerance (GI). About 24 post-GDM women were included in this study, 14 women were grouped in the GI group and 10 were grouped in the normal glucose tolerance (NGT) group according to oral glucose tolerance test. Macronutrient intake assessment using a three-day dietary record, anthropometric measurements, biochemical analyses, and fecal sampling were done during three to six months postpartum. Gut microbiota profiling was determined using 16S rRNA genes targeting the V3-V4 regions. The relationships between macronutrient intakes, gut microbiota composition, and metabolic phenotypes were evaluated using Pearson’s correlation coefficient and stepwise regression analyses. In this study, most post-GDM women had significantly poor dietary fiber adherence than the nutritional recommendations. Women from the GI group have significantly higher fasting blood glucose (FBG), HbA1c, and homeostasis model assessment-estimated insulin resistance (HOMA-IR) levels compared to the NGT group. The group also showed significant elevation of high-sensitivity C-reactive protein (hs-CRP) level when compared to the normal value. Specific gut microbial taxa derived from Proteobacteria and Bacteroidetes such as Parasutterella, Aquicella, Haliscomenobacter, and Prevotellaceae_NK3B31_group were significantly abundant in the GI group compared to the NGT group. Prevotellaceae_NK3B31_group was abundant in the GI group and significantly associated with high FBG, HOMA-IR, and HbA1c levels. Low fiber and monounsaturated fatty acids intakes were associated with Lactobacillus. Meanwhile, Lactobacillus was associated with high body mass index, waist circumference, FBG, 2-hour postprandial blood glucose, and hs-CRP levels. Our study suggested that macronutrient intake is an important predictor of gut microbiota dysbiosis and is associated with obesity, low-grade inflammation, and poor glycemic control in post-GDM women. Hence, dietary intake modification to remodel gut microbiota composition is a promising T2DM preventive strategy in post-GDM women.